To Walk the Same Road: Convivial Possibilities and Ethical Affordances in Borderlands Schooling - O'Connor, Brendan (Anthropologica, 2022)
In this article, I explore how teachers and students in two distinct regions of the US-Mexico borderlands, southern Arizona and south Texas, treated social difference as an ethical affordance (Keane 2014) or a resource for moral stancetaking. Inspired by work in the anthropology of morality and ethnomethodological analyses of “accountable moral choice” (Heritage 1984, 76) in interaction, I examine how the salience of social difference can become an imaginative affordance for probing experiences of and possibilities for living with difference. When axes of social differentiation became relevant to ongoing interaction, participants used them to frame their own actions or others’ actions as morally admirable, justifiable, or questionable. At times, they did so in ways that foreclosed possibilities for conviviality; at other times, their “ordinary” ethical activity (Das 2012) suggested new possibilities for dealing with social difference in diverse contexts. The analysis testifies to the “internally riven” nature of the moral universe (Keane 2011, 173)—the different stances available to be taken up, even in relation to the same people and the same objects of evaluation—and underscores that conviviality is better viewed not as a lasting state of affairs, but as a provisional interactional achievement and a site of struggle and contradiction.